2018
DOI: 10.1016/j.jtcvs.2018.01.093
|View full text |Cite
|
Sign up to set email alerts
|

Predicting kidney disease progression in patients with acute kidney injury after cardiac surgery

Abstract: The degree of acute kidney injury can identify patients who will have a higher risk of progression to acute kidney disease. These patients may benefit from close follow-up of renal function because they are at risk of progressing to chronic kidney disease or end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 13 publications
1
32
1
Order By: Relevance
“…We read with great enthusiasm the comments of Kalisnik and colleagues on our article published in the Journal 1 as they reflected on future directions of our research. In our study, 1 we found that progression to acute kidney disease (AKD) by 2 to 4 weeks after cardiac surgery can be predicted by early postoperative serum creatinine changes when using the KDIGO (Kidney Disease: Improving Global Outcomes) acute kidney injury stages. AKI represents a subchronic disease state with significant implications for patient mortality, need for renal replacement therapy (as our study demonstrated), and quality of life.…”
Section: Discovery Of Biomarkers That Diagnose Kidney Disease Progresmentioning
confidence: 80%
See 1 more Smart Citation
“…We read with great enthusiasm the comments of Kalisnik and colleagues on our article published in the Journal 1 as they reflected on future directions of our research. In our study, 1 we found that progression to acute kidney disease (AKD) by 2 to 4 weeks after cardiac surgery can be predicted by early postoperative serum creatinine changes when using the KDIGO (Kidney Disease: Improving Global Outcomes) acute kidney injury stages. AKI represents a subchronic disease state with significant implications for patient mortality, need for renal replacement therapy (as our study demonstrated), and quality of life.…”
Section: Discovery Of Biomarkers That Diagnose Kidney Disease Progresmentioning
confidence: 80%
“…AKI represents a subchronic disease state with significant implications for patient mortality, need for renal replacement therapy (as our study demonstrated), and quality of life. 1 We found that 67.9% of patients with previously normal kidney function and 81.4% of those with preexisting chronic kidney disease (CKD) had progression to AKD after cardiac surgery if postoperative acute kidney injury (AKI) was diagnosed according to the KDIGO definition. Moreover, we also found that among those patients in whom the diagnostic criteria for postoperative AKI were not met, 32.1% with normal preoperative kidney function and 18.6% with preexisting CKD developed progressive kidney disease (AKD).…”
Section: Discovery Of Biomarkers That Diagnose Kidney Disease Progresmentioning
confidence: 99%
“…This study of Mizuguchi and colleagues 5 provides a framework for further research in understanding the progression of kidney disease after cardiac surgery. As an observational retrospective study, there are many limitations, including the fact that the analysis was performed on only 20.5% of the study population and the assumption that the patients who did not have creatinine measured at weeks 2 through 4 (79.5%) were healthier and did not require close follow-up.…”
mentioning
confidence: 92%
“…Further characterization of AKI as transient (<48 hours) versus persistent (48 hours-7 days) is also gaining momentum, because the window for recovery is small. 4 In their article in this issue of the Journal, Mizuguchi and colleagues 5 have sought to narrow this knowledge gap by using these definitions to understand the frequency and impact of AKD in a large, retrospective, multiyear observational study of more than 10,000 adult cardiac surgical patients at a single institution. They found that at baseline, 68% (n ¼ 6952) of the entire cohort had no known kidney disease and 32% (n ¼ 3282) had preexisting CKD.…”
mentioning
confidence: 99%
See 1 more Smart Citation